Composição físico-química e cor de clones de mandioquinha-salsa - Carmo, Ezequiel Lopes do [UNESP]; Leonel, Magali [UNESP] (EIA Energy in Agriculture, 2012)
This study aimed to characterize the physical and chemical composition of ten items of arracacha grown in the municipality of São Manuel for the 2009 harvest. In the roots of the clones BGH (4560, 5741, 5744, 5746, 5747, 6414, 6513, 6525 and 7609) and the cultivar Amarela de Senador Amaral the characteristics evaluated were: color (L *, a * and b *) and moisture, ash, crude fiber, raw grease, protein, reducing sugars, total sugars and starch. After obtaining the data, an analysis was performed for the variance of test F and comparisons between the means made by the Tukey test at 5% probability. There was no significant difference to the results of luminosity (L *) while BGH 6414 and BGH 5744 showed the highest values for chroma and * BGH 5741, BGH 6414, BGH 7609, 'Amarela de Senador Amaral' BGH 5747 presented the highest chroma values for b *. Clones BGH 7609 and BGH 6414 showed significantly higher levels of dry matter and with the potential yield of agro-industrial processes it would be best suited in the form of frying. The materials that showed significantly larger amounts of ash were BGH 6525, BGH 5747, 'Amarela de Senador Amaral ", BGH 4560, BGH 5746, BGH 6513. Regarding the contents of fatty matter BGH 6525, BGH 5741 and BGH 5744 showed the highest levels. The results of BGH 7609 showed crude fiber significantly higher than the other materials tested, it can be used in diets composed of fibers. BGH 4560 and cultivar had the highest crude protein. BGH 5741 showed the lowest reducing sugar content among the clones, but not significantly different from results found for the cultivar. All clones showed total sugar levels were higher in the cultivar, which may have more flavor. BGH 5741, BGH 5746, BGH 6525 and BGH 6513 showed significantly higher starch content than the cultivar Amarela de Senador Amaral. From these results we conclude that the clones have similar color characteristics, and are potentially a nutritionally adequate substitute for the cultivar.

Este trabalho teve por objetivo caracterizar quanto à composição físico-química dez materiais de mandioquinha-salsa cultivados no município de São Manuel, safra de 2009. Nas raízes dos clones BGH (4560, 5741, 5744, 5746, 5747, 6414, 6513, 6525 e 7609) e no cultivar Amarela de Senador Amaral as características avaliadas foram: cor (L*, a* e b*) e teores de umidade, cinzas, fibra bruta, matéria-graxa, proteína bruta, açúcares redutores, açúcares totais e amido. Após a obtenção dos dados foi realizada a análise de variância pelo teste F e as comparações entre as médias feitas pelo teste de Tukey, em nível de 5% de probabilidade. Não houve diferença significativa para os resultados de luminosidade (L*) ao passo que BGH 6414 e BGH 5744 apresentaram os maiores valores para croma a* e BGH 5741, BGH 6414, BGH 7609, ‘Amarela de Senador Amaral’ e BGH 5747 apresentaram os maiores valores para croma b*. Os clones BGH 7609 e BGH 6414 apresentaram teores de matéria secas significativamente superiores, podendo ser potenciais para rendimento em processos agroindustriais, sendo indicadas para processamento na forma de fritura. Os materiais que apresentaram quantidades significativamente superiores quanto aos teores de cinzas foram BGH 6525, BGH 5747, ‘Amarela de Senador Amaral’, BGH 4560, BGH 5746 e BGH 6513. Quanto aos teores de matéria graxa, BGH 6525, BGH 5741 e BGH 5744 apresentaram os maiores teores. BGH 7609 apresentou resultado de fibra bruta significativamente superior aos demais materiais avaliados, podendo ser utilizado em dietas compostas de fibras. BGH 4560 e o cultivar apresentaram os mais altos teores de proteína bruta. BGH 5741 apresentou o menor teor de açúcares redutores dentre os clones, porém não diferiu estatisticamente do resultado encontrado para o cultivar. Todos os clones apresentaram teores de açúcares totais superiores ao do cultivar, os quais podem apresentar mais sabor. BGH 5741, BGH 5746, BGH 6525 e BGH 6513 apresentaram teor de amido significativamente superior ao do cultivar Amarela de Senador Amaral. A partir dos resultados obtidos foi possível concluir que os clones avaliados apresentam características de cor semelhantes, são potencialmente nutritivos, podendo substituir o cultivar.
Measurement of some physiochemical components in clones of arracacha
Keywords: Arracacia xanthorrhiza Bancroft; Color; pH and acidity; Proimate composition; Arracacia xanthorrhiza Bancroft; Cor; pH e acidez; Composição centesimal